Type and Potential Sources of Polycyclic Aromatic Hydrocarbons (PAHs) in Coastal Area of Tarakan City, North Borneo, Indonesia - Ratno Achyani; Dietriech G Bengen; Tri Prartono; Etty Riani; Abdullah Hisam bin Omar (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
PAHs are mutagenic and carcinogenic agents that influence the coastal water of Tarakan City. This study aims to determine the concentration, type, and distribution of PAHs in waters and sediments of rivers, seawater, and brackish ponds, and their potential sources. Fourteen samples of water and sediment from selected stations obtained 14 types of PAHs priority (USEPA). Analysis using GC-MS Type Thermo Trace 1310 single quadrupole Mass Spectrometer, using Coulum melting silica column (coulumn fused silica) DB5 MS with a length of 30 m, a diameter of 0.32 mm inline. The concentration in sediments at river locations ranges from 0.72-352.84, between 1.23-606.74 in the sea, and brackish ponds 0.08-2858.88 ng.g-1. On the waters ranged from 42.46-160.25 µg.L-1, in the sea 7.95-167.55 µg.L-1 and ponds 7.63-151.60 µg.L-1. The concentration level in rivers and seas is small and in the ponds is small-very high. The concentration on water at the river site was observed to increase from upstream to downstream. Meanwhile in sediment was higher in the upstream decreased towards the middle of river and increased in downstream/estuary area. The concentration in the Tarakan coastal environment signifies the potential hazards to the environment. Components Nap, Fla, Pyr, Chr, and BaP are types that are often identified. Furthermore, two, four and five rings of PAHs were shown to dominate in water and sediment, with the major rings present in both river and brackish pond. The PAHs were both petrogenic and pyrolytic sources from land base sources that were possibly derived from the Pamusian river.